Boron-doped copper self-supporting electrode and preparation method thereof

Through simple boron doping treatment on the copper electrode, the problems of complex preparation process and high reaction conditions of doped copper self-support electrode are solved, and the ammonia generation with high selectivity and stability are achieved, with huge industrial application prospects .

CN119265600APending Publication Date: 2025-01-07CHINA THREE GORGES RENEWABLES (GRP) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411684143.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing doped copper self-supporting electrodes have complex preparation processes, high reaction conditions requirements and difficult to disperse doped materials evenly, which limits their application in industry.

Method used

Boron atom doping is performed on foamed copper with high specific surface area by one-step immersion method, and boron is simply doped on the copper electrode through immersion of sodium borohydride solution. The process is simple and the conditions are mild, making it convenient for large-scale production.

Benefits of technology

The gradual hydrogenation of nitrate reduction products has been achieved, catalytic activity and selectivity have been improved, the selectivity of ammonia gas generation has reached 95%, and the synthetic ammonia yield has reached 2.8mmol h-1 cm-2, which has good stability and is suitable for industrial-grade applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265600A_ABST
    Figure CN119265600A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of functional materials, and particularly relates to a boron-doped copper self-supporting electrode and a preparation method thereof. The preparation method comprises the following steps: removing impurities and an oxide layer on the surface of foamy copper, then immersing the foamy copper into a sodium borohydride solution, and after doping is completed, cleaning and drying the foamy copper. The one-step simple doping synthesis method is adopted, operation is easy, industrial quantitative production can be achieved, the foamy copper is subjected to an immersion reaction, boron atoms are doped on the foamy copper with the high specific surface area through an in-situ substitution method, doping is uniform, meanwhile, more active hydrogen supply is provided for the electro-catalysis nitrate reduction reaction, and the method is suitable for industrial production. Gradual hydrogenation of nitrate reduction products is promoted, catalytic activity and selectivity are improved, and the prepared electrode has great industrial application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional materials technology, specifically relating to a boron-doped copper self-supporting electrode and its preparation method. Background Technology

[0002] In order to cope with NO3 - The severe challenges posed by pollution have led to the extensive exploration and application of processes such as reverse osmosis, ion exchange, electrocatalysis, electrodialysis, and biological denitrification. Among these processes, clean electrical energy is used to remove NO3 at the cathode. - Catalytic reduction to N2, ammonia (NH3), and other compounds has attracted increasing attention. Among these reduction products, NH3 is the most attractive due to its wide range of applications in agriculture, hydrogen-rich fuels, and the synthesis of fine chemical products.

[0003] Due to NO3 - The low dissociation energy of the N=O bond (204 kJ mol⁻¹) in NO₃⁻ - Reduction to NH3 has theoretically significant advantages. However, NO3... - The reduction to NH3 involves 8 electrons and 9 protons, therefore, many potential reaction pathways may occur during this process, producing a variety of products (NO2, NO3-, NO2-). - Understanding the basic steps and catalytic principles of catalysis (such as NO, N2, NH3, and N2H4) allows for the study of the optimal catalysts for the selective formation of NH3. Existing research indicates that NO3... - Adsorbed on the catalyst, it gains 2 electrons and is reduced to nitrite (NO2). - ), then NO2 - It gains electrons and undergoes hydrogenation to produce NH3. Based on this molecular-level mechanism, selecting a suitable catalyst for the selective production of NH3 requires consideration of the appropriate NO3 content. - Adsorption and further hydrogenation. Due to NO3 - The lowest unoccupied molecular orbital (LUMO) π* orbital, copper-based materials are considered to be highly active adsorbents of NO3. - Cu is the best catalyst material and has been used as a self-supporting electrode in the preparation of NH3. However, if only Cu is used as a catalyst, NO3... - The reduction reaction will remain in the first stage, resulting in a large amount of NO2 as a byproduct. - Accumulation hindered subsequent hydrogenation reactions.

[0004] Previous reports have shown that combining Cu-based nanomaterials with transition metals or noble metals with high hydrogen evolution performance, or doping Cu-based nanomaterials with highly electronegative nonmetals, can enhance the supply of hydrogen intermediates in the reaction medium, thereby enhancing the selectivity of NH3 formation. However, existing doped copper self-supporting electrodes generally face the problem that the dopant material is difficult to disperse uniformly on the electrode, and the preparation process is complex, requiring high reaction conditions, making large-scale synthesis difficult, which seriously limits their application in practical industry. Summary of the Invention

[0005] This invention provides a method for preparing a boron-doped copper self-supporting electrode. This method can dope boron onto a copper electrode through a simple soaking operation. The method is simple, has low process requirements, and is easy to prepare on a large scale.

[0006] This invention provides a boron-doped copper self-supporting electrode that can promote the stepwise hydrogenation of nitrate reduction products, exhibiting high catalytic activity and selectivity.

[0007] This invention also provides the application of the boron-doped copper self-supporting electrode prepared above in the electrocatalytic reduction of nitrate to synthesize ammonia, which has great potential in the fields of water treatment and ammonia synthesis.

[0008] The present invention achieves the above-mentioned technical objectives through the following technical solutions:

[0009] This invention provides a method for preparing a boron-doped copper self-supporting electrode, comprising the following steps:

[0010] Remove impurities and oxide layers from the surface of the foamed copper, then immerse it in a sodium borohydride solution. After doping, clean and dry to obtain the final product.

[0011] In the preparation method described above, the concentration of sodium borohydride solution is 0.1-1 mol / L, and the doping time is 12-24 h.

[0012] In the preparation method described above, the reaction temperature is ≤50℃, preferably 15-30℃ or room temperature.

[0013] The preparation method described above, wherein the method for removing impurities and oxide layer from the surface of the copper foam is as follows: cleaning the copper foam with organic solvents or acid solutions; and / or

[0014] The organic solvent is selected from acetone and ethanol, and the acid solution is selected from hydrochloric acid and sulfuric acid.

[0015] In the preparation method described above, when the acid solution is selected from hydrochloric acid, the concentration of the dilute hydrochloric acid solution is 2-5 mol / L.

[0016] The preparation method described above, wherein the method for removing impurities and oxide layer from the surface of the foamed copper is as follows: the foamed copper is ultrasonically washed in acetone solution, rinsed with deionized water, then ultrasonically washed in dilute hydrochloric acid solution, rinsed with deionized water, and dried; and / or

[0017] Copper foam was ultrasonically washed in acetone solution for 20-40 minutes and then ultrasonically washed in dilute hydrochloric acid solution for 10-20 minutes.

[0018] As described above, the sodium borohydride solution is used after being ultrasonicated until homogeneous.

[0019] The present invention also provides a boron-doped copper self-supporting electrode, comprising copper foam and boron atoms doped on the surface of the copper foam; and / or

[0020] It was prepared using the method described above.

[0021] The present invention also provides a method for electrocatalytic reduction of nitrate to synthesize ammonia, specifically using the above-mentioned boron-doped copper self-supporting electrode as the working electrode.

[0022] The method for preparing boron-doped copper self-supporting electrodes provided by this invention employs a one-step immersion and in-situ substitution doping method to dope boron atoms on high specific surface area copper foam. The method is simple to operate, easy to industrialize, and produces uniform doping.

[0023] The boron-doped copper self-supporting electrode provided by this invention exhibits extremely high selectivity and catalytic activity for ammonia generation, achieving high performance at industrial-grade current densities (300 mA cm⁻¹). -2 Under these conditions, the selectivity for ammonia synthesis reached 95%, and the maximum ammonia yield reached 2.8 mmol / h. -1 cm -2 The stability remained good within 100 hours, and both the ammonia Faraday efficiency and selectivity remained stable at 100 cm⁻¹. 2 Even with a large electrolyzer, its Faraday efficiency remains at 75%, corresponding to a yield of 17 mmol / cm³. -2 h -1 .

[0024] The boron-doped copper self-supporting electrode prepared by the method of this invention has great potential for practical industrial application in the electrocatalytic reduction of nitrate to ammonia synthesis, and will play a significant role in water treatment and ammonia synthesis. Attached Figure Description

[0025] Figure 1 This is a schematic diagram of the process for preparing a boron-doped copper self-supporting electrode according to the present invention;

[0026] Figure 2The X-ray diffraction (XRD) patterns of the boron-doped copper self-supporting electrode (Cu-B) and the original foamed copper electrode (Cu) prepared in this invention are shown.

[0027] Figure 3 Scanning electron microscope (SEM) and high-resolution transmission electron microscope (HR-TEM) images of the boron-doped copper self-supporting electrode (Cu-B) and the original copper foam electrode (Cu) prepared in this invention;

[0028] Figure 4 The above images show the X-ray photoelectron spectroscopy (XPS) spectra of the boron-doped copper self-supporting electrode (Cu-B) prepared in this invention, where image a represents B1s, image b represents O1s, and image c represents Cu2p.

[0029] Figure 5 The figures show the Faradaic efficiency of ammonia, nitrate, and hydrogen, and the ammonia yield of the boron-doped copper self-supporting electrode (Cu-B) and the original foamed copper electrode (Cu) prepared in Example 1 of this invention, under different nitrate concentrations (0.1-2.0M). Figure a shows the Faradaic efficiency of ammonia, figure b shows the Faradaic efficiency of nitrate, figure c shows the Faradaic efficiency of hydrogen, and figure d shows the corresponding ammonia yield.

[0030] Figure 6 The boron-doped copper self-supporting electrode (Cu-B) and the original foamed copper electrode (Cu) prepared in Example 1 of this invention are compared at 300 mA / cm. 2 Stability of performance testing under high current density;

[0031] Figure 7 The scan voltammetry (LSV) curves are those of the boron-doped copper self-supporting electrode (Cu-B) and the original foamed copper electrode (Cu) prepared in Example 1 of this invention.

[0032] Figure 8 This document presents a series of mechanistic analyses of the boron-doped copper self-supporting electrode (Cu-B) and the original foamed copper electrode (Cu) prepared in Example 1 of this invention. Figure a shows the Tafel curves, Figure b shows the Tafel efficiency of the nitrate reduction reaction at different concentrations, Figure c shows the logarithmic curves of the substrate concentration and current density, Figure d shows the yields of Cu-B and Cu electrodes in a heavy water environment, and Figure e shows the corresponding kinetic isotope effect values.

[0033] Figure 9 The boron-doped copper self-supporting electrode (Cu-B) and the original foamed copper electrode (Cu) prepared in Example 1 of this invention were subjected to area electrolysis (100 cm⁻¹) -2 The performance diagrams at a current of 5A are shown, where graph a is the Faraday efficiency diagram and graph b is the corresponding ammonia yield.

[0034] Figure 10 The diagram shows the ammonia Faraday efficiency of the copper self-supporting electrodes (Cu-B) with different boron doping concentrations prepared in Examples 1, 2, and 3 of this invention for the electrocatalytic reduction of nitrate to ammonia at a nitrate concentration of 0.5 M. Detailed Implementation

[0035] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0036] Existing doped copper self-supporting electrode fabrication processes are complex, require high reaction conditions, are difficult to scale up, and have difficulty uniformly dispersing doped materials on the electrode.

[0037] This invention provides a method for preparing a boron-doped copper self-supporting electrode, comprising the following steps:

[0038] Remove impurities and oxide layer from the surface of the foamed copper, then immerse it in sodium borohydride solution for 12 hours. After doping, clean and dry to obtain the final product.

[0039] This invention utilizes a one-step immersion method for in-situ substitution doping of boron atoms onto high-specific-surface-area copper foam. The method is simple, operates under mild conditions, is suitable for industrial production, and produces uniform doping. This provides a greater supply of active hydrogen for the electrocatalytic nitrate reduction reaction, promoting the gradual hydrogenation of nitrate reduction products and improving catalytic activity and selectivity. Electrochemical mechanism analysis shows that surface boron (B) doping modulates the electronic environment around Cu atoms. Its high electronegativity promotes water dissociation, enhances the supply of active hydrogen, and facilitates the subsequent hydrogenation of intermediate reduction products, thereby improving the selectivity and activity of ammonia generation.

[0040] Figure 1 This is a schematic diagram illustrating the synthesis of boron-doped copper self-supporting electrodes according to the present invention. Figure 2 The X-ray diffraction (XRD) patterns of the boron-doped copper self-supporting electrode (specifically, the Cu-B prepared in Example 1) and the original copper foam electrode (Cu) prepared according to this invention are shown. The horizontal axis represents twice the diffraction angle (degree), and the vertical axis represents the intensity (au) of the diffraction peak. Figure 2 It can be seen that the peaks of Cu-B and Cu prepared by this invention at 43°, 50° and 77° completely overlap, corresponding to the (111), (200) and (220) crystal planes of Cu, indicating that boron doping does not change the atomic structure of copper. Figure 3These are scanning electron microscope (SEM) and high-resolution transmission electron microscope (HR-TEM) images of the boron-doped copper self-supporting electrode (specifically, the Cu-B prepared in Example 1) and the original copper foam electrode (Cu) prepared according to the present invention. Figure 3 As can be seen, boron doping does not change the morphology of the original Cu, and the element distribution is uniform, indicating that the B element was successfully doped onto the Cu electrode. Figure 4 The image shows the X-ray photoelectron spectroscopy (XPS) spectrum of the boron-doped copper self-supporting electrode (specifically, the Cu-B prepared in Example 1). Figure 4 (a) It can be seen that the B1s spectra of the two electrodes are significantly different, indicating successful surface doping with B element. Figure 4 (b) It can be seen that the O1s spectrum is not significantly different. Figure 4 (c) It can be seen that the 2p of Cu-B 1 / 2 and 2p 2 / 3 The peak positions all underwent high-level shifts, indicating an increase in valence state. The strong electronegativity of B causes the valence state of Cu around the doping site to increase.

[0041] In this invention, the doping effect can be determined based on the concentration of the sodium borohydride solution and the doping time. Studies have found that the doping effect is better when the concentration of the sodium borohydride solution is 0.1-1 mol / L and the doping time is 12-24 h. The doping effect is even better when the concentration is 0.2-0.5 mol / L and the doping time is 12-17 h.

[0042] In this invention, the temperature of the doping reaction is not overly restricted; typically, a temperature of ≤50℃ is used. Further, a temperature range of 15-30℃, or even room temperature operation, can be employed. This temperature condition facilitates industrial-scale production.

[0043] After doping is complete, remove the copper foam, rinse it with deionized water or distilled water, and then dry it in an oven. It can then be used directly as a self-supporting electrode.

[0044] According to the present invention, the copper foam used for surface doping can be pre-cleaned to remove surface impurities and oxide layers, depending on the cleanliness level. Any feasible conventional method can be used, such as cleaning the copper foam with organic solvents or acid solutions. Treatment with organic solvents can remove impurities from the surface of the copper foam, while treatment with acid solutions can remove the oxide layer. After surface cleaning, the copper foam is more conducive to in-situ doping of boron atoms. In some specific embodiments, the organic solvent is selected from acetone and ethanol, and the acid solution is selected from hydrochloric acid and sulfuric acid. When hydrochloric acid is used as the acid solution, the concentration can be selected as 2-5 mol / L, for example, 2 mol / L, 3 mol / L, 4 mol / L, or 5 mol / L.

[0045] When removing impurities and oxide layers from the surface of foamed copper, the surface impurities are usually removed first, followed by the oxide layer. In some specific embodiments, the method for removing surface impurities and oxide layers from foamed copper is as follows: the foamed copper is ultrasonically washed in acetone solution, rinsed with deionized water, then ultrasonically washed in dilute hydrochloric acid solution, rinsed with deionized water, and dried.

[0046] There are no particular limitations on the power and time of ultrasonic cleaning of copper foam in organic solvents and acid solutions, as long as impurities or oxide layers are completely removed. Typically, ultrasonic cleaning in organic solvents takes 20-40 minutes, and in acid solutions takes 10-20 minutes. In some specific embodiments, ultrasonic cleaning in organic solvents takes 30 minutes, and in acid solutions takes 15 minutes, with conventional ultrasonic power such as 200-500W being sufficient.

[0047] When preparing sodium borohydride solution, it should be stirred and then sonicated until homogeneous before use to ensure uniformity.

[0048] Understandably, the foamed copper needs to be cut to fit the size of the electrolyzer. The cutting of the foamed copper usually occurs before the removal of impurities and oxide layers. In other words, commercially available foamed copper is first cut to the required size before impurity removal, oxide layer removal, and boron doping.

[0049] This invention also provides a boron-doped copper self-supporting electrode, comprising copper foam and boron atoms doped on the surface of the copper foam. Further, it can be prepared by the method described above. The self-supporting electrode of this invention operates in a 0.5M nitrate concentration electrolyte and at an industrial-grade current density of 300 mA / cm². -2 Below, the Faraday efficiency (FE) of ammonia production NH3 Up to 95%, nitrite Faraday efficiency (FE) NO2- The efficiency was only 1.4%, significantly better than that of unmodified commercial foamed copper self-supporting electrodes (FE). NH3 83%, FE NO2- (10%). Meanwhile, the electrode is at 300 mA cm⁻¹. -2 The FE achieved a 100-hour stability test. NH3 It stabilizes at 90-95%, with minimal voltage fluctuations.

[0050] Meanwhile, compared with the Cu foam@Cu2O catalyst described in the article "Boosting electrochemical nitrite–ammonia conversion properties by a Cu foam@Cu2O catalyst" published in Chemical Communications on December 7, 2021, the boron-doped copper self-supported electrode showed that the Cu foam@Cu2O catalyst achieved a maximum Faradaic efficiency of 94.21% for ammonia synthesis in 0.1 M nitrite solution, corresponding to a yield of 7.5 mg / h. -1 cm -2 The current method is far inferior to the boron-doped copper self-supporting electrode (Cu-B) in this invention. The Cufoam@Cu2O catalyst is prepared by washing commercially available copper foam with 3M hydrochloric acid, then using it as the anode in a 0.5M oxalic acid electrolyte solution for oxidation at 5V for 5 minutes, with a platinum electrode as the cathode. Afterwards, it is removed, rinsed, and calcined in a tube furnace under an argon atmosphere at 550°C for 1 hour to obtain the final product.

[0051] The present invention also provides a method for electrocatalytic reduction of nitrate to synthesize ammonia, comprising using the above-mentioned boron-doped copper self-supporting electrode as the working electrode.

[0052] The preparation method of boron-doped copper self-supporting electrode and the obtained product are described in detail below with reference to specific embodiments:

[0053] Example 1

[0054] This embodiment provides a method for preparing a boron-doped copper self-supporting electrode. Figure 1 The preparation process is illustrated below:

[0055] Step 1: Wash the commercial foam copper and cut it to the appropriate size (2cm x 2cm for 1cm). 2 In the membrane electrode assembly, the cut copper foam is first placed in acetone solution and ultrasonically washed for 30 minutes to remove surface impurities. Then, the ultrasonically washed copper foam is washed with deionized water and placed in 4 mol / L dilute hydrochloric acid solution and ultrasonically washed for 15 minutes to remove surface oxide impurities. After washing in the same way, it is finally placed in an oven to dry.

[0056] Step 2: Place the copper foam into a 0.3 mol / L sodium borohydride solution, ensuring it is completely submerged in the liquid. React at room temperature for 12 hours. After removal, rinse with deionized water and then dry to obtain a boron-doped copper self-supporting electrode (denoted as Cu-B).

[0057] Example 2

[0058] This embodiment provides a method for preparing a boron-doped copper self-supporting electrode. Figure 1 The preparation process is illustrated below:

[0059] Step 1: Wash the commercial foam copper and cut it to the appropriate size (2cm x 2cm for 1cm). 2 In the membrane electrode assembly, the cut copper foam is first placed in acetone solution and ultrasonically washed for 30 minutes to remove surface impurities. Then, the ultrasonically washed copper foam is washed with deionized water and placed in 2 mol / L dilute hydrochloric acid solution and ultrasonically washed for 15 minutes to remove surface oxide impurities. After washing in the same way, it is finally placed in an oven to dry.

[0060] Step 2: Place the copper foam into a 0.1 mol / L sodium borohydride solution, ensuring it is completely submerged in the liquid. React at room temperature for 12 hours. After removal, rinse with deionized water and then dry to obtain a boron-doped copper self-supporting electrode.

[0061] Example 3

[0062] This embodiment provides a method for preparing a boron-doped copper self-supporting electrode. Figure 1 The preparation process is illustrated below:

[0063] Step 1: Wash the commercial foam copper and cut it to the appropriate size (2cm x 2cm for 1cm). 2 In the membrane electrode assembly, the cut copper foam is first placed in acetone solution and ultrasonically washed for 30 minutes to remove surface impurities. Then, the ultrasonically washed copper foam is washed with deionized water and placed in 5 mol / L dilute hydrochloric acid solution and ultrasonically washed for 15 minutes to remove surface oxide impurities. After washing in the same way, it is finally placed in an oven to dry.

[0064] Step 2: Place the copper foam into a 0.8 mol / L sodium borohydride solution, ensuring it is completely submerged in the liquid. React at room temperature for 12 hours. After removal, rinse with deionized water and then dry to obtain a boron-doped copper self-supporting electrode.

[0065] Application Example 1

[0066] In the membrane electrode assembly (MEA) electrolyzer (1cm) 2 Performance evaluation was conducted using the boron-doped copper self-supporting electrode prepared in Example 1 as the cathode electrode and commercially available nickel foam as the anode electrode, separated by an anion exchange membrane (AEM) and electrolysis tests were performed.

[0067] The cathode electrode solution consisted of 50 mL of 1.0 M potassium hydroxide solution mixed with potassium nitrate of different concentrations (0.1, 0.5, 1.0, and 2.0 M), while the anolyte was 50 mL of 1.0 M potassium hydroxide solution. Before testing, nitrogen gas was bubbled into the electrolyte for 30 minutes to purge dissolved oxygen and reduce the influence of the oxygen reduction competition reaction at the cathode. Cross-current mode testing was conducted using an external DC power supply at 100, 200, 300, 500, and 700 mA cm⁻¹. -2 Electrolysis was performed at five current densities at room temperature for 1 hour. Voltage changes were recorded. After the reaction was completed, the cathode electrolyte was removed, diluted to a reasonable range (200-400 times), and quantitative analysis was performed using ultraviolet spectrophotometry (UV-vis).

[0068] Application Example 2

[0069] In a flow-cell electrolyzer (1cm) 2 Electrochemical mechanism analysis was performed using an effective electrolysis area: a three-electrode system and a Shanghai Chenhua electrochemical workstation (760E) were used for testing. The boron-doped copper self-supporting electrode prepared in Example 1 was used as the working electrode, commercial nickel foam was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The anode and cathode were separated by an anion exchange membrane (AEM) and electrolysis tests were performed.

[0070] The cathode electrolyte consisted of 50 mL of 1.0 M potassium hydroxide solution mixed with potassium nitrate of different concentrations (0.1, 0.5, 1.0, and 2.0 M), while the anolyte was 50 mL of 1.0 M potassium hydroxide solution. Before testing, nitrogen gas was bubbled into the electrolyte for 30 min to purge dissolved oxygen and reduce the influence of the oxygen reduction competition reaction at the cathode. Linear scan voltammetry was performed at room temperature using an electrochemical workstation, with a test potential of 0–1 V (for the Ag / AgCl electrode) and a scan rate of 10 mV / s.

[0071] Application Example 3

[0072] Electrolytic cell using large-area membrane electrode assembly (100cm²) 2 Performance tests were conducted to evaluate the industrial application potential of the boron-doped copper self-supporting electrode prepared in Example 1: the performance tests were performed using the same method as in Example 1, the only difference being that the electrode size used was 11 × 11 cm. 2 The anode and cathode electrolytes were 300 mL each, and the test currents were 1, 2, 3, 4, and 5 A.

[0073] Comparative Example 1

[0074] Except for replacing the cathode electrode with the original commercial foamed copper electrode, the other specific operating methods are exactly the same as in Application Example 1.

[0075] Comparative Example 2

[0076] Except for replacing the working electrode with the original commercial foamed copper electrode, the other specific operating methods are exactly the same as in Application Example 2.

[0077] Comparative Example 3

[0078] Except for replacing the cathode electrode with the original commercial foamed copper electrode, the other specific operating methods are exactly the same as in Application Example 3.

[0079] Results analysis:

[0080] Figure 5 The figures show the Faradaic efficiencies of ammonia, nitrate, and hydrogen, and the ammonia yield of the boron-doped copper self-supported electrode (Cu-B) and the original foamed copper electrode (Cu) prepared in Example 1 of this invention, under different nitrate concentrations (0.1-2.0 M). Figure 5a shows that Cu-B exhibits higher selectivity for ammonia production regardless of current density and nitrate concentration. Meanwhile, the lower nitrite Faradaic efficiency of Cu-B in Figure 5b and the slightly higher hydrogen Faradaic efficiency in Figure 5c both indicate that B doping facilitates water dissociation and nitrite hydrogenation, thereby enhancing ammonia production selectivity. Figure 5d shows the corresponding ammonia yield, which can be seen that at a suitable nitrate concentration (0.5 M), the ammonia yield reaches as high as 2.8 mmol / cm³. -2 h -1 .

[0081] Figure 6 The boron-doped copper self-supporting electrode (Cu-B) and the original foamed copper electrode (Cu) prepared in Example 1 of this invention were subjected to a 300 mA cm⁻¹ test. -2 Stability of performance testing at high current densities. As can be seen from the figure, the commercially prepared Cu electrode exhibits good stability. After boron doping, the voltage of the Cu-B electrode decreases, the ammonia Faraday efficiency increases, and the stability remains at 100 h.

[0082] Figure 7 The scan voltammetry (LSV) curves (linear scan rate: 10 mV / s, cathode electrolyte: 0.5 M potassium nitrate + 1.0 M potassium hydroxide, anolyte: 1.0 M potassium hydroxide) of the boron-doped copper self-supporting electrode (Cu-B) and the original foamed copper electrode (Cu) prepared in Example 1 of this invention are shown. As can be seen from the figure, regardless of whether potassium nitrate is present at the cathode, the current density of Cu-B is superior to that of the Cu electrode. When potassium nitrate is added to the cathode, the current density increases significantly, reflecting the reduction of nitrate ions at the cathode and the superior electrochemical activity of the Cu-B electrode.

[0083] Figure 8This document presents a series of mechanistic analyses of the boron-doped copper self-supported electrode (Cu-B) and the original foamed copper electrode (Cu) prepared in Example 1 of this invention. Figure 8a shows the Tafel curves. In the first stage, the Tafel slope for the reduction of nitrate to nitrite is less than that for the hydrogenation of nitrite in the second stage, indicating that both Cu-B and Cu have excellent adsorption and reduction capabilities for nitrate to nitrite. In the second stage, the Tafel slope of Cu-B is 113.9 mV / dec, which is less than that of Cu (145.4 mV / dec), indicating that Cu-B has a more favorable hydrogenation effect, leading to the selective conversion of nitrite to ammonia. Figure 8b shows the Tafel efficiency of the nitrate reduction reaction at different concentrations. It can be seen that in the concentration range of 0.1-2.0 M, the Faradaic efficiency of Cu-B is lower than that of Cu. Figure 8c shows the logarithmic curves of the substrate concentration and current density. It can be seen that the fitting slopes are 0.25 and 0.27, respectively, satisfying the quasi-first-order reaction relationship. Figure 8d shows the yields of Cu-B and Cu electrodes in a heavy water environment. The 8e figure shows the corresponding kinetic isotope effect values, further verifying the water dissociation capability. As can be seen from the figure, since the yield of Cu-B is higher than that of Cu electrode, the KIE value of Cu-B (kinetic isotope effect) is lower than that of Cu. This indicates that the Cu-B electrode has a stronger water dissociation capability to provide active hydrogen, thereby promoting the selective generation of ammonia.

[0084] Figure 9 The boron-doped copper self-supporting electrode (Cu-B) and the original foamed copper electrode (Cu) prepared in Example 1 of this invention were subjected to area electrolysis (100 cm⁻¹) -2 The performance at 5A current is used to assess its industrial application potential. Figure 9a shows the Faraday efficiency, which indicates that ammonia is the main reduction product. The Cu-B electrode exhibits an ammonia Faraday efficiency of 70-75% over a 2-hour period, while the nitrite Faraday efficiency increases to 11-15%. This suggests that under large-area electrolyzer conditions, the enhanced ohmic drop prevents complete energy conversion at the electrode surface, resulting in a roughly 20% decrease in ammonia yield. This is accompanied by surface heat, incomplete nitrite conversion, and enhanced hydrogen evolution reaction. Figure 9b shows the corresponding ammonia yield; the Cu-B electrode achieves a maximum yield of 17 mmol / cm². -2 h -1 The Cu electrode, however, only has a 11 mmol / cm² value. -2 h -1 .

[0085] Figure 10 This figure shows the ammonia Faradaic efficiency of the electrocatalytic reduction of nitrate to ammonia using copper self-supported electrodes (Cu-B) with different boron doping concentrations prepared in Examples 2 and 3 of this invention at a nitrate concentration of 0.5 M. In the figure, 0.1 M represents Example 2, 0.3 M represents Example 1, and 0.8 M represents Example 3. Figure 10 The differences in ammonia Faraday efficiency under different boron doping concentrations can be observed. Among them, the Cu-B electrode with a moderate sodium borohydride concentration exhibits superior ammonia generation selectivity at different current densities.

[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a boron-doped copper self-supporting electrode, characterized in that: The following steps are involved: Impurities and oxide layer on the surface of the foam copper are removed, and then it is immersed in a sodium borohydride solution. After the doping is completed, it is cleaned and dried to obtain the foam copper.

2. The method according to claim 1, characterized in that The concentration of the sodium borohydride solution is 0.1-1 mol / L, and the doping time is 12-24h.

3. The method according to claim 1 or 2, characterized in that: Reaction temperature ≤50℃.

4. The method according to claim 3, characterized in that The reaction temperature is 15-30°C or room temperature.

5. The method according to claim 1 or 2, characterized in that: The method for removing impurities and oxide layer on the surface of the copper foam is: washing the copper foam with an organic solvent or an acid solution; and / or The organic solvent is selected from acetone and ethanol, and the acid solution is selected from hydrochloric acid and sulfuric acid.

6. The method according to claim 5, characterized in that When the acid solution is selected from hydrochloric acid, the concentration of the hydrochloric acid solution is 2-5 mol / L.

7. The method according to claim 5, characterized in that The method for removing impurities and oxide layer on the surface of the foam copper is as follows: the foam copper is ultrasonically cleaned in an organic solvent, then rinsed with deionized water, then ultrasonically cleaned in an acid solution, then rinsed with deionized water, and dried; and / or The foamed copper is ultrasonically washed in an organic solvent for 20-40 min and in an acid solution for 10-20 min.

8. The method according to claim 1 or 2, characterized in that: The sodium borohydride solution was homogenized by sonication before use.

9. A boron-doped copper self-supporting electrode, characterized in that: comprising copper foam and boron atoms doped on the surface of the copper foam; and / or The method is prepared by any one of claims 1 to 8.

10. A method for synthesizing ammonia by electrocatalytic reduction of nitrates, characterized in that: The boron-doped copper self-supporting electrode according to claim 9 is used as a working electrode.